OVERVIEW OF FOOT SENSORY SENSITIVITY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AFTER PERFORMING DIABETIC FOOT EXERCISES USING A BALL AS A MEDIUM - Yulinar Maghfirah; Nurul Pujiastuti; Budiono; Nurul Hidayah (The SDGS Forum Communication, 2025)
Type 2 diabetes mellitus is a chronic metabolic disorder that can lead to complications such as peripheral neuropathy, characterized by decreased sensory sensitivity in the feet. One recommended non-pharmacological intervention is diabetic foot exercise using a ball as a medium. This study aims to describe changes in foot sensory sensitivity in patients with type 2 diabetes following diabetic foot exercise therapy using a ball. A descriptive case study approach was employed involving two two elderly participants with diabetic neuropathy. The intervention consisted of six sessions over two weeks, with each session lasting 15–20 minutes. Evaluation was conducted using the 10g monofilament test and in-depth interviews. The results indicated an increase in the number of sensation points detected after the intervention. Subjectively, both patients reported reduced tingling and lighter discomfort in the feet. These findings suggest that diabetic foot exercise using a ball can stimulate peripheral nerves and improve blood circulation. This foot exercise can be performed regularly by individuals with type 2 diabetes mellitus to maintain good sensory sensitivity in the feet and ensure optimal nerve function.